Analisis Pengaruh Aglomerasi Industri, Jumlah Industri Besar, dan Human Capital Investment Terhadap Pertumbuhan Ekonomi di Provinsi Pulau Jawa dalam Perspektif Ekonomi Islam: Analisis Data Panel Tahun 2018-2023 - Anggun Selfi Febriyani; Muhammad Kurniawan; Is Susanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Economic growth is the increase in the ability of an economy to produce goods and services, which is usually measured by the changes in Gross Regional Domestic Product (GRDP) or real national income over time. Economic growth reflects continuous quantitative changes towards better economic conditions and is one of the key indicators of the success of development in a region. The objective of this research is to determine and analyze the impact of Industrial Agglomeration, Number of Large Industries, and Human Capital Investment on Economic Growth in the Province of Java Island during the years 2018-2023. This research is a quantitative study using secondary data obtained from the Central Statistics Agency (BPS). The analysis technique used in this study is panel data regression analysis with the selected model being the Common Effect Model (CEM). The research results show that industrial agglomeration has a negative but insignificant impact on economic growth in the Province of Java Island. The number of large industries has a negative and significant impact on economic growth in the Province of Java Island. Human capital investment has a positive and significant impact on economic growth in the Province of Java Island. Together, industrial agglomeration, the number of large industries, and human capital investment influence economic growth in the Province of Java Island from 2018 to 2023.